A Study on Single-Mode Charger Using DC modeling Equivalent Estimation of the Battery - Kim, Byeong-Kak; Park, Seong-Mi; Park, Sung-Jun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, with the increase of DC devices like mobile phones and the appearance of smart grid equipped with a means of storage with possible energy time slot drift, demands for devices have increased. Because of serious risks, like explosion in overcharge for the typical battery of energy storage devices, studies of battery charging method are actively conducted.Methods/Statistical analysis: The representative battery charging method is the CC-CV charging method, which charges the battery in CC mode in early charging to shorten the battery charging time and charges it in CV mode to prevent battery overcharge in the end of charging. CV charge operates when there is a little difference between supply voltage and battery voltage and can charge over 95%, since the battery is continuously charged by the current determined by supply voltage, battery voltage and battery internal impedance. However, CV charge has a weakness that it takes much time to charge the battery fully since there is little electricity supplied to it. Findings: This study excludes the CV charging method that requires much charging time and proposes a charging method to complete charging the battery only with the CC charging method. For this purpose, this study proposes a simplified algorithm that can estimate a battery voltage by estimating the battery parameter necessary for CC charge. In addition, this study verified the validity of the proposed method through simulations.Improvements/Applications: This study proposed simplified modeling of a battery for CC and its parameter charging method to complete charging only with the CC charging method in order to shorten the charging time. In addition, through simulations, the validity of the proposed method was verified.Â Â